Alpha Amylase, Alpha Glucosidase Inhibition and Profiling of Volatile Compounds of Biologically Active Extracts from Momordica cymbalaria (Hook, Fenzl) Skin and Seeds - E. Abbirami; L. Dinesh Kumar; R. Guna; Gayathri, N.; Sivasudha, T. (Asian Journal of Engineering and Applied Technology, 2019)
Momordica cymbalaria (Hook, Fenzl) has been used in traditional medicine for diabetes in India. This study was designed to examine, total phenolic, total flavonoid contents and in vitro anti-oxidant activity by using seven different types of solvent extracts. The biologically active extracts, ethanol extract of fruit skin (EESK) and methanol extract of seed (MESE) were evaluated for in vitro anti-diabetic activity followed by detection of bioactive metabolites by GC-MS analysis. EESK and MESE exhibited IC50 values of 185.1 μg/ml against α – amylase and 224.4 μg/ml against α – glucosidase, respectively. GC-MS profiling of skin and seed portion of the vegetable revealed the presence of 40 compounds from EESK and 29 compounds from MESE. Thus, this study reveals that EESK and MESE exhibited in vitro anti-diabetic activity and GC-MC profiling confirms the presence of anti-diabetic phytocompounds such as L-Cysteine and cis- Vaccenic acid.